Do Green Innovations stimulate Employment? Firm-level Evidence From Germany - Georg Licht; Bettina Peters (WWWforEurope, 2014)
This paper studies the impact of environmental innovation on employment growth in the period 2006-2008 using firm-level data for German manufacturing and services. It extends the model by Harrison et al (2008) in order to distinguish between employment effects of environmental and non-environmental product as well as process innovation. As a robustness check patent data on green technologies are employed. The results demonstrate that both environmental and non-environmental product innovations stimulate employment growth. We find a similar gross employment effect of both types of product innovations. That is, one-percent increases in sales stemming from new environmental and non-environmental products increase gross employment by one percent each. Thus, we do not find evidence that that new products with environmental benefits for consumers are produced with higher or lower efficiency than old products. Yet, the net employment contribution of non-green product innovations is 4 to 5 times larger than the net contribution of green product innovations. This is the result of differences in the average innovation engagement and innovation success of both types of new products. In contrast, environmental and non-environmental process innovation plays only a little role for employment growth. In particular, we do not identify a significant trade-off between more environmental-friendly production technologies and employment growth. This holds for both cleaner production technologies and end-of pipe technologies.
Keywords: O33; J23; L80; C21; C23; 330; Employment growth; environmental innovation; green patents